Additive manufacturing of bimetallic structures - Bandyopadhyay, Amit; Zhang, Yanning; Onuike, Bonny (Virtual and physical prototyping, 2022)
Current industrial applications demand materials with customised features and site-specific properties, and many such applications use bimetallic structures. Bimetallic structures offer unique properties from both materials. Bimetallic materials are made by joining two different materials via welding or brazing. Although welding techniques to join two metallic materials are economical, there are still many critical issues, such as managing the heat-affected zone, cracking, and premature failures due to brittle intermetallic phase formation, especially for joining two dissimilar metals, and reproducibility. In recent years, metal additive manufacturing (AM) has been explored towards processing bimetallic materials. Metal AM systems are designed with multiple feedstock materials, enabling various printing strategies to process bimetallic structures. This review aims to aid researchers in understanding AM processing of bimetallic structures. Various processing strategies, characterisation methods, challenges, and future directions are discussed. We envision that this review will help further the implementation of AM technologies in bimetallic structures.